2018
DOI: 10.1161/jaha.118.008759
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Burden and Correlates of Symptomatic Paroxysmal Supraventricular Tachycardia

Abstract: BackgroundContemporary data about symptomatic paroxysmal supraventricular tachycardia (PSVT) epidemiology are limited. We characterized prevalence and correlates of symptomatic PSVT within a large healthcare delivery system and estimated national PSVT burden.Methods and ResultsWe identified adults with an encounter for potential PSVT between 2010 and 2015 in Kaiser Permanente Northern California, excluding those with prior known atrial fibrillation or atrial flutter. We adjudicated medical records, ECGs, and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 11 publications
1
26
0
1
Order By: Relevance
“…7 These specific ICD-9 and ICD-10 codes were chosen as they have previously been shown to most accurately document a true diagnosis of PSVT. 5 More than one diagnosis was required in the outpatient setting to improve specificity, as diagnoses coded in the emergency department or inpatient settings tend to more reliably code for true arrhythmia episodes.…”
Section: Methodsmentioning
confidence: 99%
“…7 These specific ICD-9 and ICD-10 codes were chosen as they have previously been shown to most accurately document a true diagnosis of PSVT. 5 More than one diagnosis was required in the outpatient setting to improve specificity, as diagnoses coded in the emergency department or inpatient settings tend to more reliably code for true arrhythmia episodes.…”
Section: Methodsmentioning
confidence: 99%
“…Arrhythmias is an age-related disease (Hatch et al, 2011;Khurshid et al, 2018). For instance, the incidence of paroxysmal supraventricular arrhythmias is 14.8 per 100,000 person-years in adults aged 18 to 24 years, but in persons aged ≥65 years, the rate is increased to 231.9 per 100,000 person-years (Go et al, 2018). It is estimated that by 2050, supraventricular-related arrhythmias will affect approximately nine million individuals aged >60 years in China (Tse et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The recent PRE-EMPT study retrospectively evaluated health records of over 4.2 million people in the USA, estimating PSVT incidence at 73/100,000, and national prevalence at 168/100,000 (translating into some 393,810 affected American adults), with older and female individuals being more at risk. 1 On the other side of the Atlantic, the UK Biobank prospective population cohort study, looking at the records of 502,627 people aged 40-69, showed a baseline prevalence of PSVT at 0.28%, overall prevalence of 0.42%, and an incidence of 0.51 cases per 1,000 person-years. 2 The National Hospital Ambulatory Medical Care Survey estimated that in the USA, 50,000 emergency department visits per year were attributed to PSVT, at a cost upward of US$190 million.…”
mentioning
confidence: 99%